Determinants of customer satisfaction with artificial intelligence-enabled social media marketing in Malaysia - Ng, Ch’ng Sim; Tan, Yi Xuan (2023)
This research aims to study the factors that influence customer satisfaction in AI enabled social media marketing in Malaysia by incorporating the E-service quality model. Online questionnaires were used as the primary data collection method to collect information from 200 respondents. Data were subsequently analyzed and interpreted using correlation and multiple regression analysis. The outcomes of the research demonstrated that customer satisfaction is not influenced by website design, fulfillment, and privacy protection, but is indeed influenced by chatbot quality and personalization. Notably, personalization has the most profound influence on customer satisfaction in AI-enabled social media marketing. The research findings contributed in terms of allowing online business owners to understand the factors that customers are concerned about within the realm of AI-enabled Social Media Marketing. This study has also successfully extended the E-service quality model in the context of AI-enabled social media marketing. However, this study’s extent is only restricted to Malaysia. Hence, further research is recommended to complement it by investigating the study variables in different countries and incorporating other variables not addressed in this study.